Influence of palmitic and oleic acid mixtures on combustion evaluation of a diesel engine. (2021) - Bibin, Chidambaranathan; Devan, P.K.; Senthil Kumar, S.; Gopinath, S.; Sheeja, R.
Abstract: Diesel engines are commonly known for its high-power output and high performance. However, the rise in energy consumption, the gradual depletion of petroleum fuels and compliance with strict emission regulations are of great interest to researchers to produce alternative fuels from renewable energy resources. Of all the different alternative fuels, vegetable oil replaces traditional diesel fuels. The transesterification process is frequently used in the process of extracting biodiesel from vegetable oils. In this process, triglycerides are converted into monoglycerides using alcohol and a catalyst at a specific reaction temperature. In this experimental work, pongamia and mahua oil having a higher composition of Palmitic and oleic fatty acids are used to extract biodiesel through a transesterification using methanol and KOH catalyst. Since the combustion process in diesel engine is very complicated because of heterogeneous spray combustion. The physiochemical properties of biodiesel vary when compared to diesel fuel. It is essential to study the influence of Palmitic and oleic fatty acids on combustion parameters of diesel engines. Palmitic and oleic acids are the main fatty acids of pongamia and mahua biodiesel. This was the key inspiration for this research to understand and examine the combustion behaviour of CI engines fuelled with methyl ester containing a higher composition of Palmitic and oleic acid mixture. The experiment was performed with a diesel engine for diesel and pongamia and mahua biodiesel blends (PME25, PME50, PME75 and PME) as a fuel. The combustion parameters namely, in-cylinder pressure, the MRPR, HRR, cumulative HRR, ID and CD were evaluated. It was observed that the ID and the MRPR reduced for biodiesel than diesel due to higher cetane number of biodiesel blends showing a smoother operation of the engine. The longer combustion duration was detected for all methyl ester blends, resulting in poor engine performance for biodiesel blends.